Detectors from CdTe and CdZnTe for spectrometry gamma and alpha of radiations - V. V. Levenets; O. P. Omelnyk; A. O. Shchur; V. M. Borysenko; V. E. Kutny; A. V. Rybka; I. N. Shlyakhov; O. O. Zakharchenko (Ядерна фізика та енергетика)
Results of examination of spectrometer performances CdTe (CdZnTe) detectors are submitted at recording gamma radiations in a range of 15 - 500 keV, and alpha radiations in a range of 4 - 8 MeV. It was shown, that such detectors may be used for the solution of analytical problems with definition of elements from lanthanum up to plutonium with recording X-ray of K-series and a spectrometry of particles in the method of NRA and at identification of isotopes.